2010
DOI: 10.1242/jcs.056853
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion molecule Roughest depends on βHeavy-spectrin during eye morphogenesis in Drosophila

Abstract: SummaryCell junctions have both structural and morphogenetic roles, and contain complex mixtures of proteins whose interdependencies are still largely unknown. Junctions are also major signaling centers that signify correct integration into a tissue, and modulate cell survival. During Drosophila eye development, the activity of the immunoglobulin cell adhesion molecule Roughest (also known as Irregular chiasm C-roughest protein) mediates interommatidial cell (IOC) reorganization, leading to an apoptotic event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…b H is conspicuously associated with the ZA (Lee et al, 2010;Thomas and Kiehart, 1994;Thomas et al, 1998;Zarnescu and Thomas, 1999) and is required for its integrity (Zarnescu and Thomas, 1999). Given the growing association of b H with protein recycling (Phillips and Thomas, 2006;Williams et al, 2004) (this paper), we hypothesize that this phenotype arises from defective or inappropriate trafficking of DE-Cadherin.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…b H is conspicuously associated with the ZA (Lee et al, 2010;Thomas and Kiehart, 1994;Thomas et al, 1998;Zarnescu and Thomas, 1999) and is required for its integrity (Zarnescu and Thomas, 1999). Given the growing association of b H with protein recycling (Phillips and Thomas, 2006;Williams et al, 2004) (this paper), we hypothesize that this phenotype arises from defective or inappropriate trafficking of DE-Cadherin.…”
Section: Discussionmentioning
confidence: 73%
“…Roles for the SBMS have been demonstrated in multiple organisms and tissues including: in neuronal structure, function and membrane organization (Hammarlund et al, 2007;Hulsmeier et al, 2007;Ikeda et al, 2006;Lacas-Gervais et al, 2004;Pielage et al, 2006); in epithelial structure and stability (Lee et al, 2010;Lee et al, 1997;Thomas et al, 1998); and in muscle function (Bennett and Healy, 2008;Mohler et al, 2005). Widely regarded as a static structural element, emerging results have indicated that these proteins actually have dynamic roles in transport processes including: trans-Golgi network to plasma membrane (Kizhatil et al, 2007a); ER to Golgi (Stabach et al, 2008;Stankewich et al, 2010); at the early endosome (Phillips and Thomas, 2006); and endosome to lysosome transport (Johansson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3B), whereas the Drosophila spectrin β H preferentially interacts with PI(4,5)P2 (24). This could partially account for the targeting of these unconventional β spectrins to different cell regions or compartments.…”
Section: Differential Distribution Of Spectrin βV In Amphibian and Mamentioning
confidence: 99%